2017
DOI: 10.1111/nph.14488
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐based management of invading plant disease

Abstract: Summary Effective control of plant disease remains a key challenge. Eradication attempts often involve removal of host plants within a certain radius of detection, targeting asymptomatic infection. Here we develop and test potentially more effective, epidemiologically motivated, control strategies, using a mathematical model previously fitted to the spread of citrus canker in Florida.We test risk‐based control, which preferentially removes hosts expected to cause a high number of infections in the remaining ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 58 publications
1
57
0
Order By: Relevance
“…(). The failure of culling around infected trees to control citrus canker means that it is unlikely that a culling strategy would be used in Brazil, although this type of control can potentially be successful for plant disease (Cunniffe, Cobb, Meentemeyer, Rizzo, & Gilligan, ; Hyatt‐Twynam et al., ; Parnell, Gottwald, Gilligan, Cunniffe, & van den Bosch, ; Parnell, Gottwald, van den Bosch, & Gilligan, ; Thompson, Cobb, Gilligan, & Cunniffe, ). Gottwald et al.…”
Section: Discussionmentioning
confidence: 99%
“…(). The failure of culling around infected trees to control citrus canker means that it is unlikely that a culling strategy would be used in Brazil, although this type of control can potentially be successful for plant disease (Cunniffe, Cobb, Meentemeyer, Rizzo, & Gilligan, ; Hyatt‐Twynam et al., ; Parnell, Gottwald, Gilligan, Cunniffe, & van den Bosch, ; Parnell, Gottwald, van den Bosch, & Gilligan, ; Thompson, Cobb, Gilligan, & Cunniffe, ). Gottwald et al.…”
Section: Discussionmentioning
confidence: 99%
“…In their article, Hyatt‐Twynam et al . obtained the lowest number of removed trees with a risk‐based eradication strategy, but indicated that the complexity of this strategy might make it less transparent to stakeholders. By contrast, a variable control radius strategy could be easier for stakeholders to accept.…”
Section: Stakeholder Acceptability Of Eradication Campaignsmentioning
confidence: 95%
“…By contrast, a variable control radius strategy could be easier for stakeholders to accept. As Hyatt‐Twynam et al . point out, stakeholder acceptability merits careful attention when designing eradication strategies. Historically, eradication programs have been controversial, generating strong public opposition that has delayed or even halted interventions.…”
Section: Stakeholder Acceptability Of Eradication Campaignsmentioning
confidence: 97%
See 2 more Smart Citations